(untitled) (Genius Repository, 2023)
The paper studies electro physical properties of single crystal silicon after gradual (firstsulfur, afterwards -zinc) diffusion of impurity atoms of sulfur and zinc. The authors investigated how the Si2ZnS -structured binary compounds form in the crystal lattice of silicon and also studied the physical mechanisms of how additional thermal treatment might influence the process of formation of clusters.